(untitled) (Research, Society and Development, 2023)
Supplements are made up of vitamins, minerals and other substances and are formulated to complement the individual’s needs in case of insufficiency in a traditional diet. Caffeine (1,3,7-trimethylxanthine) is a substance that can be present in various foods naturally or inserted into them, such as food supplements. However, caffeine has stimulating effects on the functioning of the nervous system and other organs and when ingested in high doses it can cause poisoning. The aim of this article was to quantitatively analyze caffeine concentrations in dietary supplements, through UV-visible spectrophotometric reading. Quantitative and laboratory experimental research was carried out on samples collected in stores specializing in the sale of dietary supplements in the city of Belém-PA, in the period of June 2023. Three samples of dietary supplements containing caffeine in their formulation were collected. UV-Visible spectrophotometric analyzes were carried out in the UNIESAMAZ multidisciplinary laboratory. The results found in the analyzed samples show that they are within the values allowed for ingestion. However, when comparing the values of the three samples analyzed, they presented caffeine values that were different from the values specified on the labels by the manufacturer. Therefore, there is a need for greater rigor in the analysis and supervision of this type of product, as well as the presence of the pharmacist in carrying out the analyzes and in guiding the use of these products, in order to avoid poisoning and consequently risk to health.